Model Latihan Passing Bawah Bola Voli Pada Siswa Sekolah Menengah Pertama - Abrasyi, Rendy; Hernawan, Hernawan; Sujiono, Bambang; Dupri, Dupri (UIR Press, 2018)
This research and development design used two instruments to gather qualitative and quantitative data such as questionnaire and underhand pass of Volleyball test. There were 10 stages of this research; (1) need analysis (2)prototype product model (3) developing product and implementation stages (4) expert validation (5) revision (6)expended field testing(7) product revision (8) operational field testing (9) final product (10) spreading product widely. The effectiveness test through pre-test got mean score about 51.00 and post-test got mean score about 72.05, so it can be concluded that developingexercise model of underhand pass of volleyball had improvement which was proved by comparing the result of students’ pre-test and post-test significantly. As conclusion, this model is acceptable to use for Volleyball exercise in junior high school level.